The Impact of Foreign Workers (TKA) on Local Workers Local Workers in South Kalimantan - Ummi Kalsum; Freti Anggriani; Alfina Damayanty (Tawazuna, 2023)
TKA is someone who comes from outside the country of Indonesia who can do work, both inside and outside the work bond to produce goods or services to meet the needs of the community. The research method used in this article is literature review, by taking an approach that involves analysis and synthesis of written sources that are relevant to the issues that have been set as the purpose of writing the article. In the country of Indonesia itself there are 111.7 thousand foreign workers, 5 Kalimantan provinces occupy positions 16, 20, 21, 22, 23. causing a significant impact from the presence of TKA to TKL in South Kalimantan. The regulations in Indonesia that regulate employment are Law Number 13 of 2003 and several Ministerial Regulations Number PPR.02/MEN/III/2008 concerning Procedures for Employing Foreign Workers. Thus it can be concluded that the influence generated by TKA on TKL does not have an impact that creates social jealousy towards TKL towards TKA.